Laser Environmental Enrichment and Spirulina Algae Improve Broiler Growth Performance and Alter Myogenic Gene Expression and pectoralis major Dimensions - Meyer, Meaghan M.; Johnson, Anna K.; Bobeck, Elizabeth A. (Frontiers in Animal Science, 2021)
Sustainability in poultry production is evident in efforts to reduce inputs and a focus on bird welfare and livability. Dietary protein alternatives to traditional sources such as soybean meal aim to meet or exceed efficiency benchmarks and be cost-effective. Environmental enrichment encouraging activity may reduce the occurrence of the predominant breast muscle myopathy, woody breast (WB); interventions to minimize muscle damage and economic loss have yet to be established. The study objectives were to maintain or improve broiler performance and breast quality through environmental enrichment and partially replacing dietary soybean meal with Spirulina. Twelve hundred Ross 708 broilers were randomly assigned to enrichment (LASER; laser enrichment, or CON; no laser enrichment) and diet (algae; 2.5% Spirulina algae, or control) in a 2x2 factorial design for 49 days. The same seventy randomly selected birds were examined for contact dermatitis wk 1-6. Breast width was measured weekly on 200 growing broilers beginning on d22. On d42 and 49 slaughter, WB score was assigned using a tactile 0-3 scale and the right breast fillet was weighed (n=200). RNA isolated from 30 breast muscle samples each at d42 and 49 was analyzed using real-time qPCR. Laser enrichment increased body weight at all timepoints (d49: 0.148 kg, P<0.001). Feed conversion ratio was improved in LASER-enriched birds by 3 points in the starter period (P=0.003). Breast width was increased at all timepoints in LASER-enriched birds compared to CON (d49: 0.47 cm, P<0.001). Algae inclusion increased body weight at d28 (0.059 kg, P=0.005). At d42, 12% more LASER-enriched WB scores were 0 (normal) compared to CON, and at d49, 15% more enriched scores were 0. At d42, 5% more algae-fed broiler scores were 0 compared to control. LASER-enriched broiler breast tissue showed upregulated expression of myogenin, muscle regulatory factor 4, insulin-like growth factor 1, and myostatin compared to CON (P<0.01). Both laser enrichment and algae inclusion improved broiler performance without negatively impacting environmental or physiological outcomes. LASER enrichment decreased severity of WB score and positively shifted myogenic gene expression in the breast muscle at slaughter.